Human Cytokine Genetic Variants Associated With HBsAg Reverse Seroconversion in Rituximab-Treated Non-Hodgkin Lymphoma Patients. Issue 11 (March 2016) - Hsiao, Liang-Tsai; Wang, Hao-Yuan; Yang, Ching-Fen; Chiou, Tzeon-Jye; Gau, Jyh-Pyng; Yu, Yuan-Bin; Liu, Hsiao-Ling; Chang, Wen-Chun; Chen, Po-Min; Tzeng, Cheng-Hwai; Chan, Yu-Jiun; Yang, Muh-Hwa; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Hepatitis B virus (HBV) reactivation has been noted in HBV surface antigen (HBsAg)-seronegative patients with CD20 + B-cell non-Hodgkin lymphoma (NHL) undergoing rituximab treatment. Clinically, hepatitis flares are usually associated with the reappearance of HBsAg (reverse seroconversion of HBsAg, HBV-RS). It is unclear whether human genetic factors are related to rituximab-associated HBV reactivation. Unvaccinated HBsAg-seronegative adults (n = 104) with CD20 + NHL who had received rituximab-containing therapy without anti-HBV prophylaxis were enrolled. Eighty-nine candidate single nucleotide polymorphisms (SNPs) of 49 human cytokine genes were chosen and were analyzed using the iPLEX technique. Competing risk regression was used to identify the factors associated with HBV-RS. Participants had a median age of 66.1 years and 56.7% were male (n = 59). The anti-HBs and anti-HBc positivity rates were 82.4% and 94.1%, respectively, among patients for whom data were available (approximately 81%). A mean of 7.14 cycles of rituximab therapy were administered, and a total of 14 (13.4%) patients developed HBV-RS. Nine SNPs showed significant differences in frequency between patients with or without HBV-RS: CD40 rs1883832, IL4 rs2243248 and rs2243263, IL13 rs1295686, IL18 rs243908, IL20 rs1518108, and TNFSF13B rs12428930 and rs12583006. Multivariate analysis showed that ≥6 cycles of rituximab therapy, IL18 rs243908, and the IL4 haplotype rs2243248∼rs2243263 were independently associated with HBV-RS. The IL4 haplotype rs2243248∼rs2243263 was significantly associated with HBV-RS regardless of anti-HBs status. Polymorphisms in human cytokine genes impact the risk of rituximab-associated HBV-RS.